Supporting Health Literacy in Youth: An Insight from Academics and Practitioners - Craig Smith; Sarahjane Belton; Hannah R. Goss (Healthcare, 2026)
Background/Objectives: Health literacy is a critical determinant of health, closely linked to behaviours, outcomes, and broader social determinants. Given that young people navigate distinct social contexts and health-related challenges compared to adults, understanding how to support their health literacy development during this important period is essential for lifelong wellbeing. This study aimed to explore the perceptions of academics and community-based practitioners regarding the concept of health literacy in young people and the importance of supporting its development. Methods: Semi-structured interviews were conducted with 30 participants (academics n = 17, health and wellbeing practitioners n = 9, policy/research n = 4) based across Europe and Australasia, with experience in youth health literacy. Data were analysed using reflexive thematic analysis. Results: Three key themes were identified: (i) Building lifelong health agency: From early foundations to transitional autonomy; (ii) Navigating novel health changes; and (iii) Structural inequities and intergenerational barriers in health literacy. Conclusions: Participants emphasised that youth health literacy interventions should move beyond didactic, individual-level information delivery toward fostering critical digital competencies and addressing structural barriers through participatory co-design with young people.